Swift and Sure: The Story of a Hydroplane - Strang, Herbert; Finnemore, Joseph, 1860-1939 (Salt Lake City, UT : Project Gutenberg, 2012)
"Swift and Sure: The Story of a Hydroplane" by Herbert Strang is a novel written in the early 20th century. The story follows the adventures of a young engineer, Will Pentelow, who becomes entangled in the tumultuous backdrop of revolutionary Venezuela while pursuing his passion for engineering and innovation through the construction of a hydroplane. The narrative combines elements of adventure, engineering, and the political unrest of the time, providing an action-packed experience for readers. The opening portion of the novel establishes a vivid and atmospheric setting along a river in the Venezuelan jungle, where a jaguar and an Indian man are introduced in a tense moment of predator and prey. As the jaguar leaps to catch the swimmer, Will Pentelow, aboard his hydroplane, intervenes, showcasing his bravery and the innovative aspect of his vessel. The scene transitions to introduce Will's background as he embarks on a railway construction project amidst a brewing revolution. The initial chapters depict both his exploration of the engineering challenges in the wild and his interactions with local characters, setting the stage for further conflicts and adventures in a country marked by political strife and personal endeavors. (This is an automatically generated summary.)
Release date is 2012-03-14
Produced by Al Haines
Keywords: Adventure stories; Venezuela -- Juvenile fiction; Hydroplanes -- Juvenile fiction